2017
DOI: 10.1017/s0007485317001080
|View full text |Cite
|
Sign up to set email alerts
|

Molecular systematics, biogeography, and colony fusion in the European dry-wood termites Kalotermes spp. (Blattodea, Termitoidae, Kalotermitidae)

Abstract: European dry-wood termites belong to the genus Kalotermes (Kalotermitidae), one of the two termite genera in Europe. Until the recent description of two new species, Kalotermes italicus in Italy and Kalotermes phoenicae in the eastern Mediterranean area, Kalotermes flavicollis was the only taxon known in this region. The presence of additional entities, suggested by morphological and physiological variation observed in K. flavicollis, was supported by molecular studies revealing four distinct genetic lineages:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…However, the taxonomy of Kalotermes is still far from being complete due to the existence of cryptic diversity within the genus, as well as undiscovered species in unsampled areas. Apart from the recently described K. italicus and K. phoenicae , Scicchitano et al (2018) showed a strong geographic structure within K. flavicollis of Western Europe, suggesting the existence of potential new species. In this study, we present new data on Kalotermes’s molecular systematics and phylogenetics, focusing on the intraspecific genetic variation of the Canarian K. dispar colonies.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…However, the taxonomy of Kalotermes is still far from being complete due to the existence of cryptic diversity within the genus, as well as undiscovered species in unsampled areas. Apart from the recently described K. italicus and K. phoenicae , Scicchitano et al (2018) showed a strong geographic structure within K. flavicollis of Western Europe, suggesting the existence of potential new species. In this study, we present new data on Kalotermes’s molecular systematics and phylogenetics, focusing on the intraspecific genetic variation of the Canarian K. dispar colonies.…”
Section: Introductionmentioning
confidence: 82%
“…The total DNA was isolated from the head using the NucleoSpin DNA Insect Mini Kit (Macherey-Nagel). Mitochondrial fragments PCR amplification was carried out with Promega GoTaq2, with thermal cycling as described in Scicchitano et al (2018) and Suárez et al (2022) , using the following primers: cox2 , C1-J-2797 (5ʹ-CCTCGACGTTATTCAGATTACC-3ʹ) and TK-N-3785 (5ʹ-GTTTAAGAGACCAGTACTTG-3ʹ) ( Simon et al 1994 ) or TL2-J-30307 (5ʹ-TAATATGGCAGATTAGTGCATTGGA-3ʹ) ( Simon et al 1994 ) and TK-N-3785 (5ʹ-GAGACCATTACTTGCTTTCAGTATCT-3ʹ) ( Gómez-Zurita et al 2000 ); rrnL , R-J-12887 (5ʹ-CCGGTCTGAACTCAGATCACGT-3ʹ) and LR-N-13398 (CGCCTGTTTAACAAAAACAT) ( Simon et al 1994 ; Palumbi 1996 ). After the amplified fragments’ purification with an ExoSap kit (Invitrogen), Sanger sequencing was performed at Macrogen Europe.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is growing interest in the genetic structures of termite populations [ 30 ], biogeography, and phylogeny, with recent studies of Heterotermes and Kalotermes [ 31 , 32 ]. Inbreeding is an integral part of the colony life cycle in many species, and has been the focal point in discussions of the evolution of eusociality in the group [ 33 ].…”
Section: Discussionmentioning
confidence: 99%